Let's Get Real about Using Economic Data - Peter Christoffersen; Eric Ghysels; Norman R. Swanson (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
We show that using data which are properly available in real time when assessing the sensitivity of asset prices to economic news leads to different empirical findings than when data availability and timing issues are ignored. We do this by focusing on a particular example, namely Chen, Roll and Ross (1986), and examine whether innovations to economic variables can be viewed as risks that are rewarded in asset markets. Our findings support the view that data uncertainty is sufficiently prevalent to warrant careful use of real-time data when forming real-time news measures, and in general when undertaking empirical financial investigations involving macroeconomic data.
Keywords: 330; Wirtschaftsindikator; Makroökonomik; Risiko; Theorie